Monogeneans from Pangasiidae (Siluriformes) in Southeast Asia: VII. Six new host-specific species of Thaparocleidus Jain, 1952 (Ancylodiscoididae) from Pangasius polyuranodon - Pariselle A.; Lim L.H.S.; Lambert A. (Parasite, 2004)
The examination of gill parasites from Pangasius polyuranodon Bleeker, 1852 (Siluriformes, Pangasiidae) revealed the presence of six new host-specific species of Monogenea, all belonging to Thaparocleidus Jain, 1952 (Monogenea, Ancylodiscoididae) as defined by Lim (1996) and Lim et al. (2001): T. caestus n. sp., T. crassipenis n. sp., T. legendrei n. sp., T. levangi n. sp., T. slembroucki n. sp. and T. virgula n. sp.